Influence of S/C ratio and temperature on steam reforming of model biogas over a metal-foam-coated Pd–Rh/(CeZrO2–Al2O3) catalyst. (1st January 2015) - Roy, Partho Sarothi; Raju, Arun S.K.; Kim, Kiseok
Graphical abstract: Highlights: S / C ratio and temperature influenced steam-biogas reforming over the Pd–Rh/metal foam catalyst. CH4 conversion was affected by both steam reforming and dry reforming of CH4 . CO2 conversion was affected by competition between dry reforming of CH4 and WGS/RWGS. S / C  = 1.50 and 1023 K were selected as optimum reaction condition for the performance guideline. SBR catalytic stability was maintained for 200 h in the accelerated run at the optimum condition. Abstract: A model biogas consisting of 60% CH4 and 40% CO2 was reformed by steam at 101.3 kPa pressure over a metal-foam-coated 1.31 wt% [Pd(7)–Rh(1)]/(CeZrO2 –Al2 O3 ) catalyst in a tubular reactor at GHSV 10, 000 h −1 . Reactant conversion, product selectivity, process thermal efficiency and coke formation were evaluated by varying S / C ratio as 1.00–2.00 in the temperature range of 923–1123 K. CO2 in the biogas as well as steam reacted to reform CH4, whose conversion was significantly contributed by dry reforming at 973 K for S / C ratio of 1.25 or 1.50. Dry reforming contribution was attenuated by steam reforming as S / C ratio or reaction temperature increased. H2 /CO selectivity increased and CO/(CO + CO2 ) selectivity decreased as S / C ratio increased; the former decreased and the latter increased as reaction temperature increased. CO2 conversion was not so high due to the competition of dry reforming with WGS/RWGS. Process thermal efficiency and coke formation were dependent upon S / C ratio and reaction temperature in a rather complicated manner. According to the performance guidelines defined in this study, S / C  = 1.50 and 1023 K were selected as optimum steam-biogas reforming condition, at which the catalytic stability was maintained for 200 h onstream period at the increased GHSV of 20, 000 h −1 .